Novel preparation of PLGA/HP55 nanoparticles for oral insulin delivery - Wu, Zhi Min (2013)
The aim of the present study was to develop the PLGA/HP55 nanoparticles with improved hypoglycemic effect for oral insulin delivery. The insulin-loaded PLGA/HP55 nanoparticles were produced by a modified multiple emulsion solvent evaporation method. The physicochemical characteristics, in vitro release of insulin, and in vivo efficacy in diabetic rats of the nanoparticles were evaluated. The insulin encapsulation efficiency was up to 94%, and insulin was released in a pH-dependent manner under simulated gastrointestinal conditions. When administered orally (50 IU/kg) to diabetic rats, the nanoparticles can decrease rapidly the blood glucose level with a maximal effect between 1 and 8 h. The relative bioavailability compared with subcutaneous injection (5 IU/kg) in diabetic rats was 11.3% ± 1.05%. This effect may be explained by the fast release of insulin in the upper intestine, where it is better absorbed by the high gradient concentration of insulin than other regions. These results show that the PLGA/HP55 nanoparticles developed in the study might be employed as a potential method for oral insulin delivery.